2012
DOI: 10.1289/ehp.1103744
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Polycyclic Aromatic Hydrocarbons and 5’-CpG Methylation of Interferon-γ in Cord White Blood Cells

Abstract: Background: Maternal factors are implicated in the onset of childhood asthma. Differentiation of naïve CD4+ T lymphocytes into pro-allergic T-helper 2 cells induces interleukin (IL)4 expression and inhibits interferon (IFN)γ expression accompanied by concordant methylation changes in the promoters of these genes. However, it has yet to be established whether maternal exposure to polycyclic aromatic hydrocarbons (PAHs) can alter these gene promoters epigenetically during fetal development.Objectives: In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 26 publications
(52 reference statements)
1
90
0
2
Order By: Relevance
“…No statistically significant changes were found in average methylation percent of all CGs among the akt1 s1, acsl3, and tm6 sf promoters. It is known that DNA methylation of a single CG (or very few) can alter gene transcription (19). Therefore, it was necessary to assess the methylation status at individual CG sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No statistically significant changes were found in average methylation percent of all CGs among the akt1 s1, acsl3, and tm6 sf promoters. It is known that DNA methylation of a single CG (or very few) can alter gene transcription (19). Therefore, it was necessary to assess the methylation status at individual CG sites.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is linked to gene activation, gene silencing, and chromosomal instability without alterations in DNA sequences. Compared to histone modifications or noncoding RNA silencing, DNA methylation studies are commonly demonstrated in both clinical studies and experimental models of lung diseases (9)(10)(11)(17)(18)(19). DNA methylation refers to the covalent addition of a methyl group derived from S-adenosyl-L-methionine to the fifth carbon of the cytosine ring to form the fifth base, 5-methyl cytosine (12).…”
mentioning
confidence: 99%
“…It has been reported that DNA methylation in a relatively small region of the Ifng promoter (that includes the -53, -205 and -297 CpG sites) controls promoter-driven Ifng expression during CD4 + T-cell differentiation [42,44]. In addition to the cytokines secreted during Th2 cell differentiation, certain environmental events such as adult exposure to diesel exhaust or developmental exposure to polycyclic aromatic hydrocarbons can alter epigenetic marks in the Ifng promoter [25,45,46]. Low to moderate levels of methylation on the Ifng promoter such as we report here following TCE exposure may allow the gene to remain 'poised' for varying levels of transcription without being silenced.…”
Section: Discussionmentioning
confidence: 99%
“…Diesel exhaust Air pollution, and more specifically diesel exhaust particles, are known to be associated with both risk for asthma and allergy [44] and changes in DNA methylation profiles [45][46][47]. Recent work assessed how in vivo exposure to diesel exhaust (through a dedicated apparatus) and allergen (through challenge within the lung) affects DNA methylation in human epithelial cells obtained by bronchoscopy.…”
Section: Impact Of Asthma-associated Exposures On the Methylome: In Vmentioning
confidence: 99%